MOG-IgG- versus AQP4-IgG-Positive Optic Neuritis in Thailand: Clinical Characteristics and Long-Term Visual Outcomes Comparison - Narongkhananukul C (Dove Medical Press, 2020)
Chanomporn Narongkhananukul,1 Tanyatuth Padungkiatsagul,1 Panitha Jindahra,2 Chaiyos Khongkhatithum,3 Lunliya Thampratankul,3 Kavin Vanikieti1 1Department of Ophthalmology, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 2Department of Medicine, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 3Department of Pediatrics, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Kavin Vanikieti Email Vanikieti.kavin@gmail.comPurpose: To compare demographic data, clinical and radiological characteristics, treatment, and long-term visual outcomes between myelin oligodendrocyte glycoprotein autoantibody-positive optic neuritis (MOG-IgG + ON) and aquaporin-4 autoantibody-positive optic neuritis (AQP4-IgG + ON) in Thailand.Patients and Methods: We included individuals who were diagnosed with either MOG-IgG + ON or AQP4-IgG + ON over an 11-year period. Demographic data, clinical and radiological characteristics at ON presentation, treatment, and long-term visual outcomes were retrospectively collected.Results: There were 16 patients (28 eyes) and 43 patients (59 eyes) in the MOG-IgG + ON and AQP4-IgG + ON groups, respectively. AQP4-IgG + ON occurred predominantly in female patients whereas MOG-IgG + ON-affected female patients and male patients equally (p < 0.001). Prior or concurrent non-ON demyelinating events were more often observed at AQP4-IgG + ON onset (p < 0.001). At ON presentation, bilaterality and the presence of optic disc edema were predominantly found in the MOG-IgG + ON group (bilaterality: 80% vs 8%, MOG-IgG + ON vs AQP4-IgG + ON patients, respectively (p < 0.001); presence of optic disc edema: 92.3% vs 36.6%, MOG-IgG + ON- vs AQP4-IgG + ON-affected eyes, respectively (p < 0.001)). There was no statistically significant difference in age at ON onset, nadir visual acuity (VA), presence of pain, segmental enhancement, and total enhanced segments of the anterior visual pathways. At the last follow-up, immunosuppressive drugs were used more often in the AQP4-IgG + ON group (43.7% vs 74.4%, MOG-IgG + ON vs AQP4-IgG + ON, respectively; p < 0.027). Remarkably better final VA was achieved in MOG-IgG + ON-affected eyes (median: 0.0 vs 0.4 logMAR, MOG-IgG + ON- vs AQP4-IgG + ON-affected eyes, respectively; p < 0.001).Conclusion: Compared with AQP4-IgG + ON, MOG-IgG + ON tended to present with bilaterality and optic disc edema and demonstrated better visual outcomes.Keywords: optic neuritis, myelin oligodendrocyte glycoprotein, aquaporin-4, neuromyelitis optica spectrum disorder, Thai